GENDER DIFFERENCE ON THE MODELING OF TURNOVER INTENTION BEHAVIOR - Rauly Sijabat (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2020)
Turnover effects on companies that tend to lead to losses as well as the results of inconclusive studies on variables that explain turnoverintention. However, studies that compare turnover intention between male and female employees on the model developed were still very limited. These empirical and theoretical findings direct this study to conduct comparative studies on male and female employees. The study was conducted on male and female employees in various industries. Interviews using questionnaires are data collection techniques used in this study. The acquisition of the data is used to test the model, the influence among variables and comparative studies using AMOS as the statistical approach. The results of the study show that turnover intention in women is higher than that of men. The high turnover intention in women is caused by the decrease in organizational commitment due to the increase in job stress.